Ferrocenyl Quinone Methide–Thiol Adducts as New Antiproliferative Agents: Synthesis, Metabolic Formation from Ferrociphenols, and Oxidative Transformation. (8th June 2016) - Wang, Yong; Richard, Marie‐Aude; Top, Siden; Dansette, Patrick M.; Pigeon, Pascal; Vessières, Anne; Mansuy, Daniel; Jaouen, Gérard
Abstract: Ferrociphenols (FCs ) and their oxidized, electrophilic quinone methide metabolites (FC‐QMs ) are organometallic compounds related to tamoxifen that exhibit strong antiproliferative properties. To evaluate the reactivity ofFC‐QMs toward cellular nucleophiles, we studied their reaction with selected thiols. A series of new compounds resulting from the addition of these nucleophiles, theFC‐SR adducts, were thus synthesized and completely characterized. Such conjugates are formed upon metabolism ofFCs by liver microsomes in the presence of NADPH and thiols. Some of theFC‐SR adducts exhibit antiproliferative properties comparable to those of theirFC precursors. Under oxidizing conditions they either revert to theirFC‐QM precursors or transform into new quinone methides (QMs) containing the SR moiety, FC‐SR‐QM . These results provide interesting data about the reactivity and mechanism of antiproliferative effects ofFCs, and also open the way to a new series of organometallic antitumor compounds.